Identification of Factors Driving Household Intention to Implement Circular Economy - Raden Danang Aryo Putro Satriyono; Dinda Safitri Ramadhani (Universitas Negeri Semarang, 2023)
Indonesia’s waste problem leads to severe effect such as economic, environment and social consequences in Indonesia as second largest contributor of plastic waste in the world. Most of the plastic waste source in Indonesia is from household sector. This phenomenon then can be further analysed with variables related to perception and behavior of humans. This study investigates determinants of residents' participation intention and behavior to implement circular economy for their plastic waste in a framework that incorporates Extended theory of planned behavior (TPB). Structural Equation Modeling (SEM) then was used to analyse all the variables correlation, The results of this study are that there are 5 significant correlations between variables, namely Descriptive Norm and Attitude have a significant and negative effect on Intention to Use. This study also found that the factors Perceived Behavioral Control, Individual concern and perceived economic use had a positive and significant effect. In addition, other findings are that Perceived Usefulness and Perceived Effectiveness and perceived environmental knowledge do not have a significant effect on Intention to Use.